Viral Evasion Strategies in Type I IFN Signaling – A Summary of Recent Developments - Schulz, Katharina S.; Mossman, Karen L. (Frontiers in Immunology, 2016)
The immune system protects the organism against infections and the damage associated with them. The first line of defense against pathogens is the innate immune response. In the case of a viral infection, it induces the interferon signaling cascade and eventually the expression of type I interferon, which then causes an antiviral state in the cells. However, many viruses have developed strategies to counteract this mechanism and prevent the production of interferon. In order to modulate or inhibit the interferon signaling cascade in their favor, viruses have found ways to interfere at every single step of the cascade, for example by inducing protein degradation or cleavage, or by mediate protein polyubiquitinylation. In this article we will review examples of viruses that modulate the interferon response and describe the mechanisms they use.